Phosphoprotein Gene Contributes to the Enhanced Apoptosis Induced by Wild-Type Rabies Virus GD-SH-01 In Vitro - Tian, Qin; Wang, Yifei; Zhang, Qiong; Luo, Jun; Jiang, He; Zhang, Boyue; Mei, Mingzhu; Wu, Fan; Wu, Yuting; Peng, Jiaojiao; Long, Teng; Luo, Yongwen; et al. (Frontiers in Microbiology, 2017)
Previous research demonstrated that the matrix protein (M) and glycoprotein (G) of attenuated rabies virus (RABV) strains are involved in the induction of host cell apoptosis. In this work, we show that wild-type (wt) RABV GD-SH-01 induces significantly greater apoptosis than the attenuated strain HEP-Flury. In order to identify the gene(s) accounting for this phenotype, five recombinant RABVs (rRABVs) were constructed by replacing each single gene of HEP-Flury with the corresponding gene of GD-SH-01. By using these rRABVs, we found that not only M and G, but also the phosphoprotein (P) plays an important role in inducing apoptosis. In order to figure out the different role of P gene in inducing apoptosis from the highly divergent background, another rRABV rGDSH-P, which carries the P gene of HEP-Flury in the background of the GD-SH-01 was generated, It was found that infection of NA cells with GD-SH-01 or the recombinant strain rHEP-shP, which carries P gene of GD-SH-01, induced significantly greater apoptosis than HEP-Flury or rGDSH-P in a caspase-dependent pathway that ultimately leads to the activation of the intrinsic apoptotic pathway, which is well characterized with the downregulation of bcl-2, the decrease of mitochondrial membrane potential, the release of mitochondrial cytochrome c, the activation of caspase-9 and caspase-3, and finally the cleavage of PARP. Our results imply that wt P from GD-SH-01 mediates this effect may partly by facilitating viral RNA synthesis but not by viral replication. In sum, we demonstrate a wt RABV strain GD-SH-01 to induce stronger apoptosis than an attenuated RABV HEP-Flury and propose that wt P from GD-SH-01 is involved in this process.